A novel exopolysaccharide-producing bacterium, Pseudescherichia liriopis sp. nov. isolated from Liriope platyphylla, enhances the growth of Daucus carota subsp. sativus under drought and salinity stress - Kim, Inhyup; Woo, Haejin; Chhetri, Geeta; Park, Sunho; Seo, Taegun (Frontiers in Plant Science, 2024)
Biological and abiotic stresses in plant growth are associated with reduced crop yields.Therefore, improving plant stress resistance can be a crucial strategy to improve crop production. To overcome these problems, plant growth-promoting bacteria are emphasized as one of the alternative tools for sustainable agriculture. This study found a novel strain (L3 T ) of a plant growth-promoting bacterium in fermented Liriope platyphylla fruit. Strain L3 T showed the ability to promote plant growth. The L3 T strain promoted plant growth of D. carota subsp. sativus, increasing the length (Increase rate compared to the control group, 36.98%), diameter (47.06%), and weight of carrots (81.5%), ultimately increasing the edible area. In addition, we confirmed that plant growth was improved even in situations that inhibited plant growth, such as salinity and drought stress. Strain L3 T performed indole production, siderophore production, phosphate solubilization, and nitrogen fixation, all characteristics of a strain that promotes plant growth. Genome analysis revealed genes involved in the growth promotion effects of strain L3 T . Additionally, the properties of EPS were identified and characterized using FTIR, TGA, and UHPLC. Our results demonstrated that L3 isolated from fermented L. platyphylla fruit can be used to simultaneously alleviate drought and NaCl stress. (1.5%), Na2MoO4•2H2O (0.2%), FeSO4•7H2O (0.01%), NaCl (0.05%), MgSO4•7H2O (0.05%), K2HPO4 (0.1%), sucrose (2.0%), and CaCO3 (0.2%). Briefly, the strain culture was plated on Jensen's medium and cultured at 25 °C for 7 days. Visual confirmation of colony growth on Jensen's medium indicates positive nitrogen fixation.